A Recent Harvest Monitoring of Cuora amboinensis in Sumatra And Kalimantan - Muhammad Alif Fauzi; Awal Riyanto; Amir Hamidy; Nia Kurniawan (Postgraduate School Universitas Brawijaya, 2021)
Harvest monitoring is an alternative strategy to determine the impacts of exploitation which is useful for conservation strategies. One of the exploited turtles, C. amboinensis in three Indonesia provinces that have high rates of turtle harvesting, North Sumatra, South Sumatra, and Central Kalimantan were moniotored and reported here. The harvest monitoring was carried out by measuring harvested specimens based on three characters comprising median carapace length (MeCL), maximum carapace width (MaCW), and biomass of turtle (Wt). The collected data were compared with the previous monitoring in 2006. This study showed that the harvested size turtle was relatively similar to that of 2006 monitoring, in North Sumatra and Central Kalimantan. Furthermore, in North Sumatra, bigger individuals and larger quantities of the juvenile were recorded whereas in Central Kalimantan the harvest characteristics showed a similar pattern compared to previous monitoring. The female individuals were dominantly harvested in all locations, with detailed sex ratio male: female 1:1.7 (North Sumatra), 1:1.6 (South Sumatra), and 1:1.1 (Central Kalimantan). In the current monitoring, there was no evidence of a decline in harvest size that might indicate that the harvest activities of C.amboinensis in Indonesia are not yet detrimental to the wild populations. However, to reveal the sustainable harvest of this species in the future, long-term monitoring and intense supervision are needed. Keywords: Cuora amboinensis, harvest size, monitoring